Lutte symbolique, recours à l’étranger et consécration transnationale. Sartre et ses modèles américains - Anna Boschetti (Transatlantica)
Sartre’s effort to assimilate the achievements of American novelists, notably Faulkner, Hemingway and Dos Passos, played a major role in his literary apprenticeship. By explicitly emphasizing this filiation, he distinguished himself from his predecessors and from competitors he faced in his own country. In turn, after 1945, thanks to the fame he gained, he did much to boost the reputation of his American masters, in France and around the world. We will reconstruct this symbolic exchange and analyze the forms of appropriation and misappropriation that Sartre practiced with respect to his models. We will also see how the transformation of his position after 1945 affected his attitude towards writers admired in his youth. On the theoretical level, we will test some general hypotheses concerning, on the one hand, the conditions of the transnational circulation and consecration of literary works (Bourdieu, 2002 ; Sapiro, 2012, 2013 and 2016b ; Casanova, 2015), and, on the other hand, the factors that determine writers’ choices, including with respect to the technical aspects of their works. In particular, we will highlight the role of symbolic struggles, showing that we can shed new light on writers’ practices by considering them as « position-taking », linked to the state of the field, locally and globally, and to the characteristics of the positions the writers occupy in it (Bourdieu, 1992).